Antioxidant Profiling of Botryocladia leptopoda Based on In Silico and In Vitro Studies - Panjaitan, Fenny Crista Anastasia; Chai, Huey-Jine (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2025)
Seaweed has long been recognized as an excellent source of antioxidants. The presence of antioxidant activity from Botryocladia leptopoda was investigated. The study aims to estimate the potential antioxidative peptides released by B. leptopoda sequences using an in-silico approach and to explore the antioxidant capacities revealed by different extracts. In silico studies using the ProtParam and BIOPEP-UWM databases showed that B. leptopoda proteins are potential sources of antioxidative peptides. Glycine and leucine were identified as the primary amino acids detected in the sequences. The antioxidant capacities of various seaweed extracts at different drying temperatures (60 °C and 70 °C) and solvents (alkaline-ethanol, ethanol, and water) were further observed in vitro. The fraction from alkaline-ethanol extraction of seaweed dried at 60 °C (BL-A, 1 mg/mL) produced a high phenolic concentration of 6.44 mg GA/g (p 0.05). It exhibited superior reducing power activity, with an absorbance of 0.29 at 700 nm (p 0.05) and ferrous ion chelating activity of 99.64% (p 0.05). In comparison, significant DPPH radical scavenging activities were observed in the ethanol extracts of seaweed dried at 60 °C (BL-B) and 70 °C (BL-C), with 46.08% and 33.74%, respectively, at a 1 mg/mL concentration (p 0.05). At a 10 mg/mL concentration, BL-B and BL-C optimally scavenged DPPH radicals (96.61% and 94.79%, respectively). Overall, this study showed that in silico and in vitro analyses yielded similar results. Thus, B. leptopoda can be considered a promising source of antioxidative products in the functional food and pharmaceutical industries.